Amphetamine Induces Oxidative Stress, Glial Activation and Transient Angiogenesis in Prefrontal Cortex via AT1-R - Basmadjian, Osvaldo M.; Occhieppo, Victoria B.; Marchese, Natalia A.; Silvero C., M. Jazmin; Becerra, María Cecilia; Baiardi, Gustavo; Bregonzio, Claudia (Frontiers in Pharmacology, 2021)
Background: Amphetamine (AMPH) alters neurons, glia and microvessels, which affects neurovascular unit coupling, leading to disruption in brain functions such as attention and working memory. Oxidative stress plays a crucial role in these alterations. The angiotensin type I receptors (AT1-R) mediate deleterious effects, such as oxidative/inflammatory responses, endothelial dysfunction, neuronal oxidative damage, alterations that overlap with those observed from AMPH exposure. Aims: The aim of this study was to evaluate the AT1-R role in AMPH-induced oxidative stress and glial and vascular alterations in the prefrontal cortex (PFC). Furthermore, we aimed to evaluate the involvement of AT1-R in the AMPH-induced short-term memory and working memory deficit. Methods: Male Wistar rats were repeatedly administered with the AT1-R blocker candesartan (CAND) and AMPH. Acute oxidative stress in the PFC was evaluated immediately after the last AMPH administration by determining lipid and protein peroxidation. After 21 off-drug days, long-lasting alterations in the glia, microvessel architecture and to cognitive tasks were evaluated by GFAP, CD11b and von Willebrand immunostaining and by short-term and working memory assessment. Results: AMPH induced acute oxidative stress, long-lasting glial reactivity in the PFC and a working memory deficit that were prevented by AT1-R blockade pretreatment. Moreover, AMPH induces transient angiogenesis in PFC via AT1-R. AMPH did not affect short-term memory. Conclusions: Our results support the protective role of AT1-R blockade in AMPH-induced oxidative stress, transient angiogenesis and long-lasting glial activation, preserving working memory performance.